feldmann and chlebek training
fact is an exciting new method for testing and training in any endurance sport. fact is the product of six years of practical research in the field. The basis of the system is a Heart Rate - Lactate test to establish heart rates used for training and racing. A sample of the test is shown on the left. The Lactate vs Heart Rate curve establishes the heart rate for the Lactate Balance Point (lowest point on the curve) and the line of Heart Rate vs Speed is used to monitor the progress the athlete makes as a result of training. The first point on the line marked by a square is called the Lower Linear Limit and the highest point on the line is called the Upper Linear Limit. The Lactate Balance Point heart rate is a dynamic value which changes with training and racing. As a result the blood lactate of an athlete must be continually monitored to prevent over-training (or in some cases, training at too low an intensity level for effective adaptation). Interpretation of the test has been made simple with a custom Windows 95 Software which produces a printout of the graphic and analysis of the test. The validity of the fact LBP has been proven in a study by a research group at the University of Bern in Switzerland. A summary of the results is shown below. Lactate monitoring has been made simple with the advent of hand held Lactate Analyzers like the Lacate Pro LT-1710. One tiny painless drop of blood from a finger gives a measurement in 60 seconds. Lactate Analysis is no longer the exclusive domain of national teams or scientific research centers. The Lactate Pro is affordable by any serious athlete, coach, or club.Feldmann and Chlebek have used the fact system for biking, cross-country skiing, running and even with exercise equipment such as stair climbers. Feldmann has had excellent results using the system to determine safe but effective levels of exercise intensity for rehabilitation of heart patients.